Survey on the occurrence of dental trauma and preventive strategies among Brazilian professional soccer players - Marcos Britto Correa; Helena Silveira Schuch; Kauê Collares; Dione dias Torriani; Pedro Curi Hallal; Flavio Fernando Demarco (University of São Paulo, 2010)
OBJECTIVES: The aims of this study were to verify the occurrence of dental injuries in professional Brazilian soccer players, the level of knowledge of the teams' medical departments about mouthguards, and the conducts adopted in cases of dental trauma during the match. MATERIAL AND METHODS: Closed questionnaires were sent to the physicians in charge of the medical departments of the 40 teams enrolled in the first and second divisions of the Brazilian professional soccer league in 2007. The data obtained were subjected to descriptive analysis to determine absolute and relative frequencies of answers for each one of the questions. RESULTS: Physicians from 38 (95%) of the 40 teams in the first and second divisions answered the questionnaires and 71.1% reported the occurrence of some type of dental injury during soccer practice, dental fractures (74.1%) and avulsions (59.3%) being the most prevalent ones. Regarding emergency conducts, approximately 50% answered that a successful replantation could be obtained in periods from 6 to 24 h after injury, and 27.8% were not able to answer this question. Regarding mouthguard use, 48.6% of the physicians did not know about mouthguards, and only 21.6% usually recommended their use by the soccer players. Among the physicians who do not recommend the use of mouthguards, 50% justified that it was not necessary. Almost 50% of the medical departments do not have a dentist as part of the health professional staff. CONCLUSIONS: It was possible to conclude that dental injuries are common during professional soccer practice and that there is a lack of information in the medical departments related to the emergency conducts and prevention of dental trauma.